ANALISIS SIMULASI PERFORMA TURBIN PROPELLER PEMBANGKIT LISTRIK TENAGA MIKROHIDRO PROFIL AIRFOIL NACA 5310 DAN NACA 6412 - Haryadi; Ahmad Zaki Rasyidi; Apri Setiawan; Budi Triyono; Setiawan, Dibyo (Badan Penerbit Universitas Muria Kudus, 2026)
Renewable energy, particularly hydropower, has become an important alternative in reducing dependence on fossil fuels. One widely used technology is the propeller turbine, which utilizes airfoil-based blade profiles to enhance the conversion of fluid energy into mechanical energy. This study aims to analyze the simulation performance of a propeller turbine with variations of NACA 5310 and NACA 6412 airfoil profiles under low-head conditions. The methodology employed is a numerical simulation based on Computational Fluid Dynamics (CFD). The observed variables include flow rate, pressure distribution, rotational speed, torque, hydraulic power, mechanical power, and turbine efficiency at head variations of 3 m and 5 m. The simulation results indicate that increasing the head from 3 m to 5 m significantly increases the flow rate, torque, and mechanical power; however, the turbine efficiency decreases drastically from approximately 69–71% at a 3 m head to about 30% at a 5 m head. The NACA 6412 profile demonstrates slightly better performance than the NACA 5310 profile, particularly in terms of efficiency and torque stability. Overall, both airfoil profiles are more suitable for low-head operating conditions and therefore have strong potential for application in micro-hydro power plants.